PENERAPAN METODE PERMAINAN BERBURU UBUR-UBUR UNTUK MENINGKATKAN MINAT PESERTA DIDIK DALAM BELAJAR MATEMATIKA SISWA KELAS II SDN BLOTONGAN 02, SALATIGA - Rana Rizqina Gunadi; Antonius Wahyana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to enhance interest in mathematics learning among second-grade students at SDN (State-Run Elementary School) Blotongan 02 Salatiga by implementing the "jellyfish hunting" game method. The research employed a Collaborative Classroom Action Research approach using the Kemmis and Taggart model. The study involved 24 students from class II B and was conducted in two cycles, utilizing questionnaires and documentation for data collection. Results demonstrated a significant improvement in students' interest in learning mathematics. In the pre-cycle phase, the average interest in mathematics learning was 75.1% with a class average score of 59. Cycle I increased to 78.7% in learning interest with a class average of 68. In cycle II, the average interest in mathematics learning reached 93.3% with a class average score of 89. Learning mastery also improved from 25% in the pre-cycle to 50% in cycle I, and 91% in cycle II. Applying the jellyfish hunting game method improved learning interest, student engagement, and understanding of mathematical concepts. This study concludes that the jellyfish hunting game method can effectively increase the interest in learning mathematics among second-grade students at SDN Blotongan 02 Salatiga.